Pengaruh Kepemimpinan, Partisipasi Masyrakat Dalam Akuntabilitas Pembangunan Desa Paan Waru Kecamatan Elar Selatan Kabupaten Manggarai Timur - Rikardus Nardin; Bonefasius Berdi (CV. ULIL ALBAB CORP, 2024)
The method used in this research is a quantitative method, this technique is used to find out how much the community is involved in activities with the village government in Paan Waru Village, with research sources using primary data and secondary data and the data collection methods used in this research are: observation, questionnaires, and documentation. Based on the results of research conducted through simultaneous hypothesis testing, it shows that leadership and community participation influence village development. with a significance value of 0.001, which means it is lower than 0.05, seen from the results of the t test for the Leadership variable with a significance value of 0.001, which means it is lower than 0.05, seen from the results of the t test for the Community Participation variable with a significance value of 0.003, which means higher than 0.05, so it can be stated that community participation has a positive effect on village development. Leadership and community participation implemented in accordance with the law can maximally influence the performance of the village government on the village development system. Meanwhile, partially the community participation variable has no effect on the village development system. This shows that community participation in Paan Waru village is quite good and has not yet reached the standard of success in the village development system.